WHAT MATTERS MOST TO THE PATIENT BEFORE AND AFTER INITIATION OF TREATMENT FOR THYROID DYSFUNCTION? - M, Mohd Azril; My, Yap; CP, Ooi; A, Abdul Hanif Khan; A, Rosliza; M, Norlaila; S, Norlela; K, Nor Azmi (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Thyroid dysfunction (TD) has a prevalence of 3.4% in Malaysia. Although there are significant disparities in the quality of life before and after treatment in many diseases, no study has been done to assess the impact of TD on patients before and after treatment. Thus, the objective of this analysis is to evaluate what matters most to patients before and after treatment of TD. METHODOLOGY This qualitative study utilised a Malay language version of the semi-structured interview guide in Malaysia. This is part of the larger research developed from interactive discussions with patients who have thyroid dysfunction. Data were collected using a dual--method approach, i.e., face-to-face in-depth interviews in the endocrine clinic and online survey using the same set of questionnaires. The responses were analyzed using Braun and Clark's thematic analysis framework guided by the question: What matters most to the patient before and after initiation of treatment for TD? RESULTS Before treatment, most patients diagnosed with TD were anxious, scared, sad, angry, and in disbelief. Other concerns include impairments in the activity of daily living, e.g. unable to cope with their jobs, a perceived burden to the family, and uncertainties. Only some were able to accept the diagnosis. Most patients feel relieved knowing there are available treatments and their conditions improved after treatment, while a minority of patients remained anxious with low mood, and in denial. Our findings suggested that patients with TD go through the five stages of emotional changes based on the Kubler-Ross model during the disease management process. CONCLUSION Our findings suggested that TD is a life event for most patients. The grief reaction towards their illness resolved with treatment and improved knowledge regarding their condition. Therefore, research that focuses on developing insight into patient issues is needed to develop appropriate management and support programs.